Postacute Sequelae of SARS-CoV-2 Infection—Lessons Learned From a Coordinated Health System Response - Ravindra Ganesh, MBBS, MD; Greg S. Vanichkachorn, MD, MPH; Bala Munipalli, MD; Sara N. Hanson, DO, MPH; Abd Moain Abu Dabrh, MBBCh, MS; Ivana T. Croghan, PhD; Nancy L. Dawson, MD; Ryan T. Hurt, MD, PhD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2022)
Objective: To outline a consensus-designed process for triaging and managing patients with post-coronavirus disease (COVID-19) syndrome at Mayo Clinic. Patients and Methods: We convened a central multidisciplinary team including members from the departments of general internal medicine, occupational medicine, physical medicine and rehabilitation, psychology, allergy and immunology, infectious disease, pulmonology, neurology, cardiology, and pediatrics and otorhinolaryngology with membership from all Mayo Clinic sites in Arizona, Florida, Iowa, Minnesota, and Wisconsin. Results: Consensus recommendations were made for the best practice guidelines on triaging and managing patients. Several innovations were agreed upon, including a postacute sequelae of COVID-19-specific appointment request form for data collection, a bioregistry, a biorepository, and a postacute sequelae of COVID-19-specific treatment program. Conclusion: Given that each clinical site had individual clinical practices, these recommendations were implemented using different models, which may provide broad applicability to other clinical settings.